Analisis Prioritas Distribusi Pupuk Bersubsidi untuk Ketepatan Sasaran Menggunakan Skoring Berbasis Sistem Informasi Geografis - Hans Andriano Pradana Huwae; Wahju Tjahjo Saputro; Murhadi Murhadi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The distribution of subsidized fertilizer plays an important role in supporting agricultural productivity; however, its implementation at the regional level still faces mismatches between allocation and actual land requirements. This study aims to determine the priority of subsidized fertilizer distribution for paddy agricultural land in Central Java Province using a scoring method based on Geographic Information Systems (GIS). The variables applied in this study include harvested area, land productivity, and elevation. The data used are secondary data obtained from the Central Statistics Agency (BPS) for the period 2022–2024. The scoring process was conducted using Microsoft Excel with a five-level ordinal scale and equal weighting for each variable. The scoring results were then integrated with spatial analysis using QGIS to produce thematic maps of fertilizer distribution priorities. The results indicate that each regency in Central Java Province has a different priority level, which is classified into low, medium, and high priority categories. Out of 35 regencies/cities analyzed, 17 regions (48.57%) were classified as high priority, 11 regions (31.43%) as medium priority, and 7 regions (20%) as low priority. Validation results show that most high-priority areas also receive relatively large amounts of subsidized fertilizer, although some discrepancies remain due to policy considerations and regional characteristics. This study demonstrates that a GIS-based scoring method can be used as a supporting tool for planning and evaluating subsidized fertilizer distribution in a more objective and spatially informed manner.